Edukasi Tentang Hipertensi Pada Masyarakat - Suleman, Happy Kurniati; Milah, Ana Samiatul; Amelia, Tianly; Zaqiah, Ade; Fuad, Mohammad Yudi (Yayasan Inspirasi El Burhani, 2024)
Introduction: Based on data on the prevalence of hypertension in Tasikmalaya Regency in 2021, Most of the hypertension found in the elderly is isolated systolic blood pressure (HST), increased systolic pressure results in a high probability of stroke and myocardial infarction even if the diastolic pressure is within normal limits. Research shows that hypertension occupies 89% of cases of patients aged 45 to 80 years. The presence of hypertension, either HST or a combination of systolic and diastolic is a risk factor for morbidity and mortality for the elderly. Hypertension is still the biggest risk factor for a number of diseases, such as stroke, heart failure, coronary disease, where its role is estimated to be greater than in people who are younger. The purpose of this community service is for the elderly to understand more about hypertension. Objective: Participants in this activity totaled 41 people with an age range of 45 to 80 years Method: This community service goes through several methods and stages consisting of the preparation stage and the activity stage Result: Based on the results of the training, it was found that there was an increase in knowledge with an average increase in post-test results of 16.5 with the highest score in the post-test being 100. Conclusion: Based on community service, after initial treatment, namely by providing pharmacological treatment and non-pharmacological treatment, namely that after being given education, the number increased significantly. Continuous education is carried out to remind that hypertension is a chronic disease that results in complications and requires adherence to diet and drug management as well as changes in lifestyle that are carried out throughout his age.